Guatemala : Country Economic Memorandum, Challenges to Higher Economic Growth - World Bank (Washington, DC, 2012)
The purpose of this Country Economic Memorandum (CEM) is to contribute to the ongoing discussion in Guatemala about means of accelerating economic growth to help achieve targets set in the 1996 Peace Accords as a key ingredient in the fight to reduce national poverty rates. Chapter I examines historical and recent developments and uses a benchmarking growth methodology to identify the measures and policies most conducive to increasing long-term economic growth. Those areas that are identified as critical on the list of priorities are developed further in separate chapters. Chapter II focuses on the important role of human capital development for growth, along with the complementary policies for improving education and health. Chapter III examines the investment climate, broadly understood, which includes governance, access to infrastructure, and financial development. Chapter IV analyzes the importance of innovation and technology adaptation for productivity growth. Chapter V looks at trade openness and the catalytic role that the recently negotiated free trade agreement with the U.S. (CAFTA) could have on the Guatemalan economy.